Recent and Prospective Adoption of Genetically Modified Cotton : A Global CGE Analysis of Economic Impacts - Anderson, Kym; Valenzuela, Ernesto; Jackson, Lee Ann (World Bank, Washington, DC, 2012)
The authors provide estimates of the economic impact of initial adoption of genetically modified (GM) cotton and of its potential impacts beyond the few countries where it is currently common. They use the latest version of the Global Trade Analysis Project (GTAP) database and model. The results suggest that by following the lead of China and South Africa, adoption of GM cotton varieties by other developing countries-especially in Sub-Saharan Africa-could provide even larger proportionate gains to farmer and national welfare than in those first-adopting countries. Furthermore, the estimated gains are shown to exceed those from a successful campaign under the World Trade Organization's Doha Development Agenda to reduce and remove cotton subsidies and import tariffs globally.